Therapeutic monoclonal antibodies in combination with pomalidomide can overcome refractoriness to both agents in multiple myeloma: a case-based approach - Bärtsch, Marc-Andrea; Hundemer, Michael; Hillengaß, Jens; Goldschmidt, Hartmut; Raab, Marc-Steffen (Hematological oncology, 2017)
In multiple myeloma (MM), the synergy between immunomodulatory drugs (IMiDs) and monoclonal antibodies (MABs) has been demonstrated in several pivotal trials. However, disease refractory to either class of compounds remains a major therapeutic challenge. We here report on 3 heavily pretreated MM patients who were refractory to pomalidomide as well as to MABs against CD38 (daratumumab) or CD20 (rituximab), respectively, but who responded to retreatment with the same agents in combination. Responses were durable with PFS of 7, 10 (ongoing), and 30 months from initiation of combination treatment. The combination of IMiDs with MABs directed against MM cell surface antigens can overcome refractoriness to both agents.